MicroRNAs and breast cancer stem cells: Potential role in breast cancer therapy. Issue 4 (26th October 2018) - Vahidian, Fatemeh; Mohammadi, Hamed; Ali‐Hasanzadeh, Mohammad; Derakhshani, Afshin; Mostaan, Masoud; Hemmatzadeh, Maryam; Baradaran, Behzad
Abstract: MicroRNAs (miRNAs) can control cancer and cancer stem cells (CSCs), and this topic has drawn immense attention recently. Stem cells are a tiny population of a bulk of tumor cells that have enormous potential in expansion and metastasis of the tumor. miRNA have a crucial role in the management of the function of stem cells. This role is to either promote or suppress the tumor. In this review, we investigated the function and different characteristics of CSCs and function of the miRNAs that are related to them. We also demonstrated the role and efficacy of these miRNAs in breast cancer and breast cancer stem cells (BCSC). Eventually, we revealed the metastasis, tumor formation, and their role in the apoptosis process. Also, the therapeutic potential of miRNA as an effective method for the treatment of BCSC was described. Extensive research is required to investigate the employment or suppression of these miRNAs for therapeutics approached in different cancers in the future. Abstract : In the present review, we characterized the function and different characteristics of breast cancer stem cells and the function of microRNAs that are related to them.